Contribución al catálogo de la flora terrícola acidófila (líquenes y briófitos) de la provincia de Madrid (España) - Casas-garcía, Silvia; Burgaz, Ana Rosa (Botanica Complutensis, 2002)
CASAS-GARCÍA, S. & BURGAZ, A. R. 2002. Contribution to the terricolous acidophilous flora (lichens and bryophytes) from the Madrid province (Spain). Bot. Complutensis 26: 9-15. Forty one terricolous taxa, 27 lichens and 14 bryophytes, are reported from 3 acidophilous holm oak woods located in the north of the Madrid province. Cladonia grayi, C. iberica, C. ramulosa and Parmelia pokornyi are new provincial records.
Keywords: lichens; bryophytes; flora; Madrid; Spain